Comparison of treatments for preventing lower urinary tract symptoms after BCG immunotherapy of bladder tumors : a systematic review and network meta-analysis - Zihao Chen; Xin Chen; Dingchao Li; Jingang jian; Chang Yao; Xuedong Wei; Jianquan Hou (BMC Urology)
Abstract Background Bacillus Calmette-Guerin (BCG) immunotherapy is the standard adjuvant treatment for high-risk, non-muscle invasive bladder cancer (NMIBC). However, BCG immunotherapy is commonly accompanied by significant lower urinary tract symptoms (LUTS) including symptoms such as urinary urgency, frequency, dysuria and pelvic pain. These symptoms can undermine treatment adherence and clinical outcomes. In this study, the treatments for preventing LUTS after BCG instillations were compared through a systemic review and network meta-analysis (NMA). Methods Eligible studies were obtained from the PubMed, Web of Science, Embase and Cochrane Library databases. We also searched the references of the included studies. Our protocol followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) checklist. We performed NMA using Review Manager 5.3 and STATA MP 18.0. Result The analysis included 6 studies with 556 participants. The results of the NMA revealed that celecoxib and prulifloxacin effectivelty reduce the incidence of LUTS including frequency, urgency and dysuria. Phenazopyridine showed the best performance in improving pelvic pain. Conclusion The NMA indicated that medications such as celecoxib, prulifloxacin and phenazopyridine are effective in reducing the incidence of LUTS after BCG immunotherapy of bladder tumors.